Pecuk: Karawitan Artwork inspired by Pecuk Kite | Pecuk: Karya Seni Karawitan Yang Terinspirasi Dari Layangan Pecuk - I Kadek Vanny Mahendra Putra (GHURNITA: Jurnal Seni Karawitan, 2024)
Pecuk is a pepanggulan percussion creation inspired by the pecuk kite. A Pecuk kite is a form of traditional Balinese kite that has two equal corners, the result of stretching two identical girlish or bantangs. Kites and flying are entertainment, believed to originate from the mythology of Dewa Rare Angon, a manifestation of Lord Shiva. The pecuk kite is also a symbol of Ulu Candra and Windu, the wijaksara or sacred script symbol of God. Cormorant kites are unique in terms of shape and when they fly. The simplicity of balance in the making and the uniqueness of flying this kite are transformed in preparing this pepanggulan percussion creation. This creation aims to be able to implement ideas taken from the local wisdom of the Balinese people (kites and hovering) into a genre of Balinese composition called Tabuh Kreasi Pepanggulan. The novelty of this pepanggulan percussion creation has been obtained through research using qualitative methods accompanied by methods for creating performing arts based on local wisdom (Rai S., 2021), which includes a process of developing talent, creativity, understanding the local culture, the concept of the work, belief and praying for the implementation of the idea. Work, trial work, and determining the form of work (IPR). Observations, interviews, and literature studies were conducted to find a progressive work concept. The creation process that most produce new percussion creations is entitled "Pecuk, using the Gong Kebyar gamelan barungan as a medium of expression. This work involved 35 musicians and was performed at the Natya Mandala Building, Indonesian Institute of the Arts Denpasar, using the aesthetic rules of performing arts such as stage design, lighting, and clothing.